ChemInform Abstract: Novel Pyrazole Integrated 1, 3, 4‐Oxadiazoles: Synthesis, Characterization and Antimicrobial Evaluation. Issue 16 (22nd April 2014) - Ningaiah, Srikantamurthy; Bhadraiah, Umesha K.; Doddaramappa, Shridevi D.; Keshavamurthy, Shubakara; Javarasetty, Chethan
Abstract Among the synthesized oxadiazole derivatives, compound (IIIh) emerges as an effective antimicrobial agent.